2016
DOI: 10.1186/s12885-016-2275-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes between luminal invasive ductal carcinoma and luminal invasive lobular carcinoma

Abstract: BackgroundThe pathological and clinical features of invasive lobular carcinoma (ILC) differ from those of invasive ductal carcinoma (IDC). Several studies have indicated that patients with ILC have a better prognosis than those with ductal carcinoma. However, no previous study has considered the molecular subtypes and histological subtypes of ILC. We compared prognosis between IDC and classical, luminal type ILC and developed prognostic factors for early breast cancer patients with classical luminal ILC.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 18 publications
9
55
1
Order By: Relevance
“…Loibl et al observed that patients with ILC had a low chance of obtaining a pCR although it was not well correlated with further outcome [20]. In another study focusing on the ER+/HER2- subgroup, patients with ILC had shorter disease-free survival and overall survival than patients with IDC [21], in congruence with our data.…”
Section: Discussionsupporting
confidence: 86%
“…Loibl et al observed that patients with ILC had a low chance of obtaining a pCR although it was not well correlated with further outcome [20]. In another study focusing on the ER+/HER2- subgroup, patients with ILC had shorter disease-free survival and overall survival than patients with IDC [21], in congruence with our data.…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with the observation that ductal tumors tend to be more aggressive and are predictive of poorer outcome19, although significance was lost when adjusted for stage, ER status, or both, which may also be consistent with other studies that have shown that lobular tumors can have similar or even worse prognosis than ductal tumors when lobular subtypes are assessed51. The 46 selected genes for the final model included E-cadherin (CDH1), which has long been recognized to be differentially expressed between lobular and ductal tumors.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we intended to investigate the relationship between the molecular subtypes proposed by the St. Gallen consensus meeting 2013 and SUVmax of primary breast cancer lesion. Because the pathological and clinical features and FDG avidity of IDC differ from those of invasive lobular carcinoma (ILC) [15], our study specifically enrolled patients with IDC to perform investigations in a homogeneous patients' group.…”
Section: Introductionmentioning
confidence: 99%